Partisipasi Relawan terhadap Kegiatan Peningkatan Minat Baca Masyarakat di Taman Baca Suka Maju Sejahtera Kota Padang - Rahayu, Ririn; Nurizzati, Nurizzati (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2018)
AbstractThe purpose of this paper is to describe the participation of volunteers in the activities of increasing reading interest in the reading park Suka Maju Sejahtera in the city of Padang, describe the constraints faced by activities to increase reading interest community, describes the efforts made by volunteers and reading park Â to the activities to increase the reading interest of the community. Data were collected through observation, interview, and video recording. Descriptive data analysis. Based on the result of research, it can be concluded as follows. first, volunteer participation in package A equivalent to elementary school, using B equivalent to junior high school, package C equivalent to high school, loan collection, drawing and coloring services, and making of dindind magazines. second, the constraints faced were inadequate facilities and infrastructure to support education, limited collections, lack of volunteers, lack of reading interest from the community, and lack of promotion. third, the efforts made are supporting facilities and infrastructure for education must be completed, additional collections, adding volunteers, socializing the importance of reading, and promoting through mass media and social media.Keyword: library, reading park , volunteer, reading interest, society.